Physical Activity During the School Day. Issue 5 (13th June 2022) - Erwin, Heather; Centeio, Erin; Reed, Julian; Stoepker, Peter
Abstract: A plethora of research has been conducted on physical activity (PA) during the school day as part of a CSPAP. Classroom activity, recess, and other school day opportunities such as active transitions, school-wide movement breaks, and drop-ins provide valuable opportunities for students to reach recommended levels of PA. In addition to the health benefits from engaging in PA during this time and decreasing bouts of sedentary behavior, positive outcomes have been demonstrated in terms of students' academic performance and social/emotional health. The purpose of this paper is to provide an overview of research conducted on PA during the school day over the past decade and offer suggestions to practitioners on efficient and effective ways to incorporate PA during school. Based on the collective efforts of researchers, we summarize the outcomes and provide the biggest "return on investment" for physical educators, classroom teachers, and PA professionals who are most likely to implement PA during the school day as part of a CSPAP.